Variability in biocontrol potential and microbial interaction of Trichoderma spp. with soil inhabiting antagonistic bacteria Pseudomonas fluorescens - SUBHENDU JASH, SITANSU PAN* (Indian Phytopathology, 2010)
Ten isolates of Trichoderma spp. collected from diverse agro-ecological habitats of West Bengal were evaluated against Fusarium oxysporum f.sp. radicislycopersici through dual culture technique and production of volatile and nonvolatile substances. T1, T7 and T10 isolates were most efficient against the test pathogen in dual culture. Similarly, T7 isolate of T. virens was highly effective against the pathogens causing 62.5% mycelia inhibition over the control by the production of volatile metabolites, where as T10 retarded 64.4% mycelia growth followed T1, T6, T2, T4 and T7 respectively which were statistically at par in their antagonistic effect by production of non volatile substances at 10% concentration. When the interaction between Trichoderma isolates and P. fluorescens on KMB was tested, the growth inhibition of biocontrol fungi was noticed upto 59.1% over control. T1 isolate of T. viride showed high level of tolerance against the Pseudomonas inhibited only 11.9% followed by T6 (13.5%) and T3 (22.4%), T5 isolate of Trichoderma was highly inhibitory against the bacterial antagonist. Inhibitory effect of P. fluorescens was comparatively more when the bacterial strain inoculated 24 h before the Trichoderma was seeded. Again significant reduction in growth of antagonistic fungus was also observed with the culture filtrate of the antagonistic bacterium even at 5% concentration. In the present investigation T6 showed highly tolerance inhibiting only 5.55% growth followed by T1 (7.03%). However in steamed soil recoverable numbers of Trichoderma population increased over the 14 days time period in all the treatments.